2013
DOI: 10.1016/j.neuropsychologia.2013.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Shape-specific activation of occipital cortex in an early blind echolocation expert

Abstract: . (2013) 'Shape-specic activation of occipital cortex in an early blind echolocation expert.', Neuropsychologia., 51 (5). pp. 938-949. Further information on publisher's website:https://doi.org/10.1016/j.neuropsychologia.2013.01.024Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in Neuropsychologia. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
54
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 52 publications
6
54
2
1
Order By: Relevance
“…Furthermore, contralateral preference is considered a typical processing characteristic of visual-motion area MTϩ (e.g., Huk et al 2002), and we found evidence for contralateral preference in temporal-occipital echo-motion ROIs in the blind experts. In combination with previous findings (Arnott et al 2013;Thaler et al 2011), the data suggest the involvement of visual cortical areas, and more specifically area MTϩ, in the processing of echo-motion in blind echolocation experts.…”
Section: Neural Reorganization For Echo-motion Processing In Blind Ecsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, contralateral preference is considered a typical processing characteristic of visual-motion area MTϩ (e.g., Huk et al 2002), and we found evidence for contralateral preference in temporal-occipital echo-motion ROIs in the blind experts. In combination with previous findings (Arnott et al 2013;Thaler et al 2011), the data suggest the involvement of visual cortical areas, and more specifically area MTϩ, in the processing of echo-motion in blind echolocation experts.…”
Section: Neural Reorganization For Echo-motion Processing In Blind Ecsupporting
confidence: 83%
“…We have found in previous research that blind echolocation experts have a relative increase in BOLD signal in occipital cortex (including calcarine cortex) during the presentation of echolocation sounds compared with echo-less control sounds (Thaler et al 2011). We have also shown that there may be a topographic representation of object shape in the calcarine cortex of an early blind echolocator (Arnott et al 2013;Thaler et al 2011). These data suggest that visual cortical areas are recruited for echolocation in blind experts.…”
Section: Neural Reorganization For Echo-motion Processing In Blind Ecsupporting
confidence: 59%
“…For example, echolocation 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 5 of moving surfaces leads to an increase in activation in temporaloccipital brain areas, potentially encroaching on visual motion area MT+ (Thaler et al, 2011(Thaler et al, , 2014. Furthermore, shape processing through echolocation is associated with activation in LOC (Arnott et al, 2013), and processing of surface materials is associated with an increase in activity in parahippocampal cortex (Milne et al, 2014a). It has also been shown that echolocation of surfaces positioned at one side can lead to a relative increase in brain activity in contralateral calcarine cortex (Thaler et al, 2011), or (for moving surfaces) in contralateral temporal-occipital brain areas (Thaler et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Skilled echolocators can reliably determine the distance and direction to objects Rosenblum et al, 2000;Schoernich et al, 2013), as well as their azimuth (Thaler et al, 2011;Wallmeier et al, 2013). They can also use echolocation to determine the shape of sound reflecting surfaces in 3D (Arnott et al, 2013;Thaler et al, 2011) and 2D (Milne et al, 2014a), as well as what materials a sound reflecting surface is made of (Arnott et al, 2013;Hausfeld et al, 1982;Milne et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation